Assessment of Quality of Life in Morbidly Obese Patients after the Bariatric Surgery - Wakil, Rafia; Batool, Sidra; Neelum Agha, Shahzadi; Abidi, Aliza; Fatima, Qandeel; Tariq, Maha (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: The global obesity epidemic presents a significant health challenge, particularly morbid obesity, which severely impacts individuals' quality of life (QoL). Bariatric surgery has emerged as a vital intervention for weight loss and improvement in comorbidities, yet its impact on QoL, especially in regions like South Asia, remains understudied. Methods: This cross-sectional study assessed the QoL of morbidly obese patients in Pakistan post-bariatric surgery, contextualizing it within global and regional obesity scenarios. Ninety-five patients who underwent mini gastric bypass surgery and sleeve gastrectomy were evaluated using validated QoL measures, including the Bariatric Analysis and Reporting Outcome System (BAROS), Modified-A Quality of Life Questionnaire II (M-A-QoLQII), and SF-36 survey. Logistic regression analyses were conducted to identify predictors of post-surgery QoL outcomes. Results: Significant improvements in QoL were observed post-surgery, with reductions in BMI and comorbid conditions. Logistic regression analyses identified age (p < 0.05), initial BMI (p < 0.05), and excess weight loss (p < 0.05) as predictors of better QoL outcomes. Despite limitations such as the single-center design and self-reported measures, the study underscores the positive impact of bariatric surgery on QoL in severely obese individuals. Practical Implication: The study highlights the importance of bariatric surgery in improving quality of life for severely obese individuals, with age, initial BMI, and weight loss predictors influencing outcomes. It supports its use for reducing BMI and comorbid conditions. Conclusion: This research contributes to understanding obesity management in Pakistan and advocates for broader access to bariatric procedures, emphasizing the importance of addressing obesity as a global health priority. Further research is warranted to explore long-term QoL outcomes and disparities in surgical access and outcomes across diverse populations.